1999
DOI: 10.1055/s-2007-979181
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Acute Suicidality in Psychiatric Inpatients Increases with Low Plasma Cholesterol

Abstract: Several studies suggest that the reduction of total cholesterol in blood by lipid-lowering agents is accompanied by a decrease in the incidence of coronary heart disease, but not in total mortality. Likewise, epidemiological studies show that low total cholesterol concentrations appear to be associated with an increased risk of death from suicide and injuries. There is little information with respect to acute suicidality and cholesterol in psychiatric inpatients; therefore the aim of the present study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 5 publications
6
29
0
1
Order By: Relevance
“…It is also possible that a low cholesterol level in suicidal patients is related with increased plasma levels of NO metabolites. Several reports showed that suicidal behavior was signifi cantly associated with low serum cholesterol levels [27][28][29] . Our group previously documented an inverse correlation between serum cholesterol level and the severity of suicide attempt [30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that a low cholesterol level in suicidal patients is related with increased plasma levels of NO metabolites. Several reports showed that suicidal behavior was signifi cantly associated with low serum cholesterol levels [27][28][29] . Our group previously documented an inverse correlation between serum cholesterol level and the severity of suicide attempt [30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…Case-control and cross-sectional studies have demonstrated lower cholesterol levels in patients admitted following suicide attempts compared to those admitted without an attempt (Takei et al, 1994;Kunugi et al, 1997;Papassotiropoulos et al, 1999;Garland et al, 2000;Sarchiapone et al, 2001;Guillem et al, 2002;Kim et al, 2002;Lee and Kim, 2003). Comparisons of suicide attempters to well controls have yielded similar results (Gallerani et al, 1995;Alvarez et al, 1999;Sarchiapone et al, 2000;Atmaca et al, 2002b;Kim et al,, 2002;Tripodianakis et al, 2002;Lee and Kim, 2003).…”
Section: Introductionmentioning
confidence: 92%
“…Case-control studies have also associated low cholesterol with other measures of suicidality including suicidal thoughts, suicidal intent, suicidal plan, or previous history of suicide attempts (Modai et al, 1994;Sullivan et al, 1994;Golier et al, 1995;Papassotiropoulos et al,, 1999). An association between low cholesterol and suicidality is not limited to individuals with major depression but has also been described in patients with borderline personality disorder (Atmaca et al, 2002a); anorexia nervosa (Favaro et al, 2004); panic disorder (Ozer et al, 2004); and schizophrenia (Atmaca et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators sampled suicide attempters from consecutive psychiatric admissions and compared them to nonattempters (Kunugi et al, 1997;Papassotiropoulos et al, 1999;Garland et al, 2000;Guillem et al, 2002), or to well controls (Gallerani et al, 1995;Sarchiapone et al, 2000;Tripodianakis et al, 2002). Others have described samples comprised specifically of patients with MDD (Modai et al, 1994;Alvarez et al, 1999;Kim and Myint, 2004), bipolar disorder (Modai et al, 1994;Bocchetta et al, 2001), panic disorder (Modai et al, 1994;Bocchetta et al, 2001;Obrocea et al, 2002;Ozer et al, 2004), borderline personality disorder (Atmaca et al, 2003) or anorexia nervosa (Favaro et al, 2004) and these also noted significantly lower cholesterol concentrations in comparison to those of nonattempters or of controls.…”
Section: Introductionmentioning
confidence: 99%